On the case report of Platypnea-orthodeoxia after SARSCoV-2 pneumonia plus historical notes - Corrêa, Paulo César Rodrigues Pinto (Acta Biomedica Atenei Parmensis, 2020)
A new cause of POS hás been recently described: SARS-CoV-2 pneumonia. Important aspects regarding the case are presented and clarifications requested from the authors. Dr Howard B. Burchell described platypnea-orthodeoxia syndrome (POS) in 1949. Burchell´s contributions to Medicine are briefly presented as well as his career.